2014
DOI: 10.1002/ijc.28791
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime risk of distinct upper aerodigestive tract cancers and consumption of alcohol, betel and cigarette

Abstract: The cancer of upper aerodigestive tract (UADT) is a common cancers in the world. However, its lifetime risk by consumption of alcohol, betel and cigarettes remain to be elucidated. This study aimed to estimate lifetime risk of distinct UADT cancers and assess their associations with alcohol, betel and cigarette consumption. Three cohorts of 25,611 men were enrolled in 1982-1992 in Taiwan. The history of alcohol, betel and cigarette consumption was enquired through questionnaire interview. Newly developed UADT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
0
21
0
4
Order By: Relevance
“…Cohort studies are less affected by recall bias, because the exposure information is obtained before the disease occurrence. The relative risk estimates of our case-control study [Oral cancer OR = 7.03, 95% CI: 4.81–10.28] and pharyngeal cancer (HR = 3.54, 95% CI: 2.09–5.98) were similar to those estimated by Hsu et al ., [19] suggesting that our study was minimally affected by recall bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohort studies are less affected by recall bias, because the exposure information is obtained before the disease occurrence. The relative risk estimates of our case-control study [Oral cancer OR = 7.03, 95% CI: 4.81–10.28] and pharyngeal cancer (HR = 3.54, 95% CI: 2.09–5.98) were similar to those estimated by Hsu et al ., [19] suggesting that our study was minimally affected by recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a cohort study of Taiwanese men, Hsu et al . reported that BQ was associated with an increased risk of oral cancer [Hazard ratio (HR) = 5.77, 95% CI: 3.60–9.25] and pharyngeal cancer (HR = 3.30, 95% CI: 1.90–5.74) [19]. Cohort studies are less affected by recall bias, because the exposure information is obtained before the disease occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…There is the longitudinal cohort study on the alcohol, betel quid, and smoking, to the oral cancer risk. The betel quid partook the significant higher hazard risk to the oral carcinogenesis [4]. The most tumorigenic part of betel quid is the Piper longum L. and the calcium hydroxide (slaked lime) which will cause the oral cavity to develop into an alkaline condition which will promote the tumorigenic effect of the Safrole in the Piper longum L. The fibers of areca also cause oral mucosa damage and increased mucosa to be exposed to the tumorigenic material in the betel quid.…”
Section: Introductionmentioning
confidence: 99%
“…First, both types of cancer are related to the same carcinogen. Studies have reported that alcohol, betel nuts, and cigarettes are independent risk predictors for distinct HNSCC and esophageal squamous cell carcinoma . Second, the underlying molecular changes in HNSCC and esophageal squamous cell carcinoma are similar.…”
Section: Discussionmentioning
confidence: 99%